Song divergence of two Bluethroat subspecies (Luscinia s. svecica and L. s. cyanecula) - Turcokova, L.; Osiejuk, T. S.; Pavel, V.; Glapan, J.; Petruskova, T. (BirdLife Finland, 2010)
As birds adapt to changing biotic and abiotic environmental conditions, parameters of their acoustic signals are modified by selective pressure for efficient communication. Such changes in song features may result in acoustic divergence among populations of the same species. We studied the divergence of songs in four populations of two genetically distinct subspecies of the Bluethroat Luscinia svecica – L. s. svecica and L. s. cyanecula. Males of svecica, occupying tundra habitats, produced less diverse songs with lower fre-quencies than cyanecula males occurring in several types of habitat. The differences in frequency parameters may be related to larger body size of the former subspecies; how-ever, habitat associations predict an opposite relationship. Contrary to expectations, rep-ertoire size did not significantly differ between the two subspecies, although cyanecula inhabits habitats with higher density and diversity of songbirds (which it may imitate). Temporal song parameters (song length, pause length, and song rate) differed signifi-cantly among populations but not between subspecies. Differences in song characteristics might be important in subspecies recognition, and may therefore contribute to the mainte-nance of subspecific differences or even influence the speciation process.